2013
DOI: 10.1182/blood-2013-09-381665
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of myelodysplasia and its clinical relevance

Abstract: Myelodysplasia is a diagnostic feature of myelodysplastic syndromes (MDSs) but is also found in other myeloid neoplasms. Its molecular basis has been recently elucidated by means of massive parallel sequencing studies. About 90% of MDS patients carry ≥1 oncogenic mutations, and two thirds of them are found in individuals with a normal karyotype. Driver mutant genes include those of RNA splicing (SF3B1, SRSF2, U2AF1, and ZRSR2), DNA methylation (TET2, DNMT3A, and IDH1/2), chromatin modification (ASXL1 and EZH2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
299
3
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(332 citation statements)
references
References 110 publications
6
299
3
11
Order By: Relevance
“…Overall, these mutation frequencies are in line with published data, except for a slightly higher frequency of CBL mutations in CMML and the absence of NRAS mutations in MDS/MPN, U. [2][3][4][5]10,[12][13][14] In previous studies the frequency of the CBL mutation was found to be ~10% in CMML instead of the 24% in our study and RAS mutations were detected in 14% of MDS/MPN, U, contrasting with the 0% in the present study.…”
Section: 1011contrasting
confidence: 50%
“…Overall, these mutation frequencies are in line with published data, except for a slightly higher frequency of CBL mutations in CMML and the absence of NRAS mutations in MDS/MPN, U. [2][3][4][5]10,[12][13][14] In previous studies the frequency of the CBL mutation was found to be ~10% in CMML instead of the 24% in our study and RAS mutations were detected in 14% of MDS/MPN, U, contrasting with the 0% in the present study.…”
Section: 1011contrasting
confidence: 50%
“…The clones are thought to be neoplastic, in that their growth is no longer compatible with normal hematopoiesis, causing ineffective production of mature blood cells, enhanced apoptosis, and even progression to AML, although the clinical presentation is highly variable. 41,42 Thus, at least conceptually, clonality is an essential requisite for the pathophysiology of MDS, but for the sake of clinical/pathological diagnosis, clinicians and pathologists usually diagnose the involvement of a neoplastic process primarily relying on cell morphology, in which the presence of excess blasts ($5%) (propensity to leukemia) and/or dysplasia (in $10% of myeloid cells) with or without increased ($15%) ring sideroblasts (deregulated myelopoiesis) empirically, but consistently, indicates that the defective hematopoiesis is caused by malignant clones, although morphologic examination may not necessarily be consistent between observers ( Figure 2). 41 Alternatively, direct demonstration of a malignant clonal process by cytogenetics can establish the diagnosis of MDS, even in the absence of dysplasia or increased blast counts, but the borderline between malignant and benign lesions is obscured: a set of abnormalities, including 27/del(7q), 25/del(5q),…”
Section: Diagnosing Mds In Aa Patientsmentioning
confidence: 99%
“…16,18,63 Somatic mutations in AA Somatic mutations are more reliable and sensitive markers for detecting clonal populations than NRXI or cytogenetics. The revolutionized technologies of next-generation DNA sequencing (NGS), together with the accumulated knowledge about the major driver mutations in MDS/AML, 42,64 have prompted investigations on somatic mutations in AA in relation to clonal evolution to MDS/AML. Thus, since the first report by Lane et al, 13 there have been several NGS-based mutation studies on AA during the past 2 years reporting varying mutation frequencies ranging from 5.3% to 72% [13][14][15][16][17][18] (Table 1).…”
Section: Skewed X-chromosome Inactivationmentioning
confidence: 99%
“…Clonal analysis based on the variant allele frequency of SF3B1 and other co-existing mutations revealed that mutations in SF3B1 are present in the dominant clone in most cases. Interestingly, the percentage of BM RS is highly correlated with SF3B1 mutant allele burden [4,[6][7][8], which strongly suggests that mutant SF3B1 directly or indirectly contributes to the formation of RS. In fact, SF3B1 mutations have a high positive predictive value for disease phenotype with RS of 97.7%, whereas the absence of these mutations has an equivalent negative prediction value [7].…”
Section: Genetic Profiles Of Rars and Mds/mpn-rs-t And Their Impact Omentioning
confidence: 82%